Evaluation of Community Pharmacy Practices in Pakistan: Insights into Asthma, Diabetes, HCV and Tuberculosis Management (Journal of Medical & Health Sciences Review, 2025)
Patient counseling is an integral part of pharmaceutical services at community pharmacies as community pharmacists are health care professionals most accessible to general public.  In this cross sectional qualitative study counseling quality of pharmacists and senior pharmacy technician was evaluated by using pseudo patient method. The study was conducted for 12 weeks at 35 community pharmacies randomly selected from various areas of Lahore. Four diseases which are most prevalent in developing countries were selected for this study. This study revealed that pharmacists were present at 52% of pharmacies visited. Counseling was offered hundred per cent on demand. On 6% pharmacies pharmacy technician refused to counsel on demand. Frequency, administration and storage of drugs were counseled frequently. Parameters like drug’s side effects, disease complications, drug interactions and contraindications were rarely addressed. Quality of counseling was much better in pharmacies where pharmacists were present, pharmacists counseled effectively about dose, frequency, administration, storage, side effects, drug interactions and complications. In order to improve quality of counseling at community pharmacies presence of pharmacist designated for patient counseling should be mandatory and continuing education programs should be run to update pharmacist and pharmacy technician knowledge.